Pengaruh Air Rendaman Rumput Fatimah (Anastatica Hierochuntica L) terhadap Frekuensi Kontraksi Otot Uterus Tikus Galur Sprague Dawley pada Fase Estrus - Nani, Desiyani (Jurnal Keperawatan Soedirman, 2009)
The frequency of contraction is one of the mechanical activities of uterine smooth muscle contractions. Recording was done without and with 0,01 IU oxytocin stimulation entered into organ bath within uterine smooth muscle strips. The aim of this research was to investigate the effect of water soaked of fatimah grass (Anastatica hierochuntica L) on the frequencies of uterine smooth muscle contractions of rattus norvegicus Sprague Dawley at the estrous phase both in without and with 0,01 IU oxytocin stimulation This research was laboratory experimental with post test only control group design. The samples were 40 uterine smooth muscle strips rattus norvegicus Sprague dawley 10-14 weeks, 150 – 250 gr weight, on the estrous stages. The rats were divided into 5 groups. Control group was treatment by vehicle of solution (water), equivalent group was treatment by estradiol, and the others were treatment by fatimah’s grass 10 gr, 20 gr, and 40 gr that soaked into 350 cc hot water (70oC) during 12 hours. Twenty hours after treatment, rats were killed, and than uterine smooth muscle was removed and connected to chymograph to record the contractions.The data was analyzed by one-way Anova and the results showed that there was no significant differences in frequencies between treatment groups and control or equivalent groups on the uterine smooth muscle strips both in with and without 0,01 IU oxytocin stimulation. And then paired t-test results showed that there were significant differences between frequencies without and with 0,01 IU oxytocin stimulation at estradiol (p=0,032), RF10 (p=0.026), RF20 (p=0,001), and RF40 (p=0,027) groups.It could be concluded that water soaked of fatimah grass (Anastatica hierochuntica L) could increased the frequencies of uterine smooth muscle contractions of rattus norvegicus Sprague Dawley at the estrous phase.